Work suffering in the team of a rural fami ly health center from the south of chile - Silva, María Cristina (Revista Chilena de Salud Pública, 2017)
This research aims to understand why workers in a rural Family Health Center (CESFAM) in the south of Chile become distressed and suffer burnout. Participants consisted of the CESFAM’s healthcare professionals, technicians, administrators, and support staff, who are tasked with providing primary healthcare to patients with physical and mental health problems. In this article, we briefly analyze theoretical and empirical literature on work distress, and later present the results of the study, which utilized case study research methodology. Data was collected through interviews, observations, and cultural artifact analysis. The results describe the transformations undergone by the CESFAM, its territory, and the population it serves, to contextualize work distress; institutional demands that affect the workers, as well as relationships and conflicts between team members, are also analyzed. This study determines that work distress is a complex, multifactorial phenomenon, originating in different institutional conditions, which affect the team’s activities and the health of individual workers.